FACTOR ASSOCIATED OF CHRONIC KIDNEY DISEASE OF UNCERTAIN ETIOLOGY: A COMPREHENSIVE SYSTEMATIC REVIEW - Natan, Andreas; Alkhaliq, Alvin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Recent interest in chronic kidney disease of non-traditional causes, also named as chronic kidney disease of unknown etiology (CKDu) has identified both individual and environmental/occupational risk factors. The aim: The aim of this study to show factor associated of chronic kidney disease of uncertain etiology. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: the results of our search get 91 articles, whereas the results of our search on SagePub get 1976 articles, on Sciencedirect 14.279 articles. Records remove before screening are 5676, so we get 10670 articles fos screening. We included five research that met the criteria. Conclusion: Different multifactorial etiologies like chronic exposure to dehydration, heat stress, agrochemicals, heavy metals, intake of fructose-rich drinks, frequent use of self-prescribed non- steroidal anti-inflammatory drugs (NSAIDS), lower income and genetics were proposed in its development.